2016
DOI: 10.1039/c5ra26502a
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the mechanism of replacement of citrate from the surface of gold nanoparticles by amino acids: a theoretical and experimental investigation and their biological application

Abstract: The present study explores the physicochemical aspects needed for the appropriate in vitro synthesis and surface modification behavior of gold nanoparticles (AuNPs) in the presence of amino acids (AA).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 48 publications
0
22
0
Order By: Relevance
“…For example, nanoparticles prepared by the approach described by Lee and Meisel are stabilized by citrate, and such stabilization is based on the electrostatic forces. Adsorption of analyte molecules can occur on the surface of citrate‐stabilized nanoparticles by substitution of citrate molecules on the silver surface or by the interaction of the analyte molecules with the citrate molecules . Another method for stabilization of nanoparticles based on steric polymer repulsion is also possible.…”
Section: Methodsmentioning
confidence: 99%
“…For example, nanoparticles prepared by the approach described by Lee and Meisel are stabilized by citrate, and such stabilization is based on the electrostatic forces. Adsorption of analyte molecules can occur on the surface of citrate‐stabilized nanoparticles by substitution of citrate molecules on the silver surface or by the interaction of the analyte molecules with the citrate molecules . Another method for stabilization of nanoparticles based on steric polymer repulsion is also possible.…”
Section: Methodsmentioning
confidence: 99%
“…There are sufficient reports indicating the safety profile of AuNPs in terms of negligible to very low cytotoxicity to various host cells/cell lines and hemolysis 4345 . A recent study has reported that coating of amino acids on the surface of AuNPs minimizes the chance of coming in contact with RBCs, hence results in reduced hemolysis 49 thus further supporting non-toxic and biocompatible nature of nanoformulations of Pep-H.…”
Section: Discussionmentioning
confidence: 81%
“…Gold nanoparticles (AuNPs) have gained considerable popularity as one of the most stable metal nanoparticles with unique electrical, optical and surface chemical properties making them applicable in fields such as sensing, drug delivery, cancer therapy and tissue engineering [1][2][3][4] . It is well known that AuNPs can be synthesized using different chemical reduction methods; out of which the citrate method introduced by Turkevich is the most widely used for the preparation of AuNPs 5,6 The biocompatible nature of citrate ion and its ability to act as a cross-linker between various ligands along with its labile nature with respect to displacement by various ligands on the surface of AuNPs render Turkevich method as one of the most popular for AuNPs synthesis 7,8 . However, in spite of the popularity and extensive usage of citrate based methods for synthesis of AuNPs 9,10 , there has been limited introspection in literature into the probable interaction between citrate and gold ions along with the structural details of citrate adsorption.…”
Section: Quantification Of Adsorbed and Dangling Citrate Ions On Goldmentioning
confidence: 99%